The Impact of Organizational Culture, Socioeconomic Status, and Previous Technology Experience on AI Learning: Mediating Role of AI Anxiety Among University Students - S, Aprilianti Nirmala; Rahman, Edi Suhardi; Fakhri, M Miftach; Surianto, Dewi Fatmarani; Baso, Fadhlirrahman; Arifiyanti, Fitria; Amukune, Stephen (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study explores the influence of AI anxiety, organizational culture, socioeconomic status (SES), and previous technology experience on AI learning outcomes among university students. Utilizing a quantitative approach, data were collected from 368 students via an online survey. Structural equation modeling (PLS-SEM) was employed to analyze the data, revealing that AI anxiety, often considered a barrier, can enhance learning outcomes when managed effectively. The study further highlights the significant direct and indirect roles of organizational culture and SES in shaping AI learning, with AI anxiety acting as a mediator. The results underscore the importance of designing educational strategies that foster a balance between institutional support and individual autonomy, while addressing disparities in technological access across different social strata. These findings offer valuable implications for developing more inclusive, accessible, and effective AI educational practices. The findings suggest that while AI anxiety is generally seen as a negative factor, its potential to motivate students when effectively managed can be leveraged to enhance learning engagement. Furthermore, the research emphasizes the need for targeted interventions and policies that ensure equitable access to AI tools, particularly for students from lower socioeconomic backgrounds, to foster a more inclusive learning environment.